ASSESSMENT OF COMPETITIVE POSITIONS ON THE LABOUR MARKET FOR BACHELORS IN THE DIRECTION “INNOVATION” IN THE FRAMEWORK OF THE “NATIONAL TECHNOLOGY INITIATIVE” - V. Degtyareva; I. Prokhorova (Вестник университета)
In the article is considered the rationale for the formation of additional professional competences for bachelors in the direction “innovation”. There is given the connection between modern trends of economic and social change and potential requests for certain competencies from the side of employers. There is considered and systematized existing competence of this area, to highlight weaknesses. There are presented the arguments to prove the need for additional professional competences within the framework of the existing program “national technology initiative” and the demands of employers.